2017
DOI: 10.1111/rec.12643
|View full text |Cite
|
Sign up to set email alerts
|

Gauging resource exploitation by juvenile Chinook salmon (Oncorhynchus tshawytscha) in restoring estuarine habitat

Abstract: In the context of delta restoration and its impact on salmonid rearing, success is best evaluated based on whether out‐migrating juvenile salmon can access and benefit from suitable estuarine habitat. Here, we integrated 3 years of post‐restoration monitoring data including habitat availability, invertebrate prey biomass, and juvenile Chinook salmon (Oncorhynchus tshawytscha) physiological condition to determine whether individuals profited from the addition of 364 ha of delta habitat in South Puget Sound, Was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…; Chittenden et al. ; Davis et al., in press). Stable isotopes determined that long‐term prey contributions and patterns of residency were at least partially responsible for these physiological differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…; Chittenden et al. ; Davis et al., in press). Stable isotopes determined that long‐term prey contributions and patterns of residency were at least partially responsible for these physiological differences.…”
Section: Discussionmentioning
confidence: 99%
“…; David et al. ; Davis et al., in press). In contrast, fish captured in EFT and freshwater tidal marshes (the majority of which were unmarked) demonstrated a greater reliance on terrestrial insects and their larvae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collective monitoring efforts in the Nisqually River Delta have shown that salmon habitat use and growth potential are affected by changes in biophysical and morphological characteristics in restored tidal channels (David et al ; Ellings et al ; Davis et al ). Our findings expand upon these results by demonstrating the added value of restoration in enhancing foraging capacity for multiple salmon species.…”
Section: Discussionmentioning
confidence: 99%